SUPPRESSOR CELLS (MDSC) REGULATE THE T-CELL RESPONSE IN OLD MICE IMMUNIZED WITH THE WHOLE-VIRION SARS-CoV-2 VACCINE - Perfilyeva , Y.V.; Abdolla , N.; Kali , A.; Tleulieva, R.; Aben , D.; Abdusattarova , Y.; Lushova, A.; Ostapchuk , Ye.; Karalnik, B.; Belyaev , N. (Eurasian Journal of Applied Biotechnology, 2024)
Myeloid-derived suppressor cells (MDSCs) are an immunosuppressive population involved in pathological processes associated with chronic inflammation. In recent years, the role of these cells in the regulation of a number of non-pathological processes, in particular, in the development of vaccine-induced immune response, has been actively discussed. This work was aimed at investigating the role of MDSC in the development of an immune response in old mice immunized with an inactivated whole virion SARS-CoV-2. Immunization of old animals induced an increase in the relative content of B cells and the production of specific antibodies to S1 and N proteins of SARS-CoV-2 in titers comparable to those of young animals. At the same time, elevated MDSC levels in aged animals negatively correlated with the level of CD8+ T cells. Splenic MDSCs in old animals were characterized by increased production of reactive oxygen species compared to young animals. In vitro experiments showed that MDSC depletion increased antigen-specific production of IFNγ by CD4+ T cells. The data obtained suggest a negative role for MDSC in regulating the T-cell vaccine-induced response to inactivated SARS-CoV-2 and encourage further studies in this direction, which may be a key to developing approaches to increase the efficacy of vaccines against SARS-CoV-2 in at-risk groups.